One in five women suffer from pelvic floor disorders in Kersa district Eastern Ethiopia: a community-based study - Merga Dheresa; Alemayehu Worku; Lemessa Oljira; Bizatu Mengiste; Nega Assefa; Yemane Berhane (BMC, 2018)
Abstract Background Hundreds of millions of women suffer from pelvic floor disorders globally, often in silence. Women in developing countries do not disclose their problems due to associated social stigma or lack of access to services. Thus, the extent of the problem remains largely unknown. This study was conducted to assess the magnitude of pelvic floor disorders in Kersa district Eastern Ethiopia. Method We conducted a community-based cross-sectional study among ever married women who reside in Kersa district, Eastern Ethiopia. The study subjects were selected through stratified multistage probability sampling. The data were collected using a structured questionnaire through face-to-face interviews. The prevalence of various pelvic floor disorders are presented along with the 95% Confidence Intervals (CI). Results A total of 3432 women participated in the study, of which 704 (20.5%; 95% CI; 19.2, 21.8) reported at least one type of pelvic floor disorder and 349 (49.6%; 95% CI: 46.0, 53.0) reported two or more pelvic floor disorders. The most common pelvic floor disorders included an over active bladder (15.5%; 95% CI: 14.4, 16.8), pelvic organ prolapse (9.5%; 95% CI: 8.5,10.4), stress urinary incontinence (8.3%; 95% CI: 7.4, 9.2) and anal incontinence (1.9%; 95% CI: 1.5, 2.4). More than two-thirds of the women with pelvic floor disorders (68.0%; 95% CI:64.4, 71.3) reported having severe distress but had never sought health care. Conclusions The magnitude of the health problem and the low level of health seeking behavior indicates the silent suffering of many women in the study area. Extrapolating these figure to national statistics would indicate the staggering number of women suffering from pelvic floor disorders in the country. This calls for urgent action to improve prevention, diagnosis and treatment services to mitigate the suffering of women from pelvic floor disorders.